Implementation and control of a hybrid non-isolated DC-DC boost converter - Goh, Cindy Wan Yi (Nanyang Technological University, 2020)
This report presents the design, implementation, and control of a hybrid non-isolated dc-dc boost converter. The hybrid non-isolated DC-DC boost converter has a higher dc voltage gain than that of the conventional boost converter. The control of the hybrid non-isolated dc-dc boost converter is carried out using a current-mode controller. The aim is to regulate the output voltage to the desired value in the presence of load and input voltage disturbances. Experimental and simulation results are provided to show the performance of the controller under different operating conditions.